Teachers’ Responses to Accountability in ABE Practice - Kimberly R. Burgess (Adult Education Research Conference, 2005)
Accountability policies in most states strongly shape how adult education literacy is defined and delivered in adult education programs. This paper examines how teachers in this study respond to the pressure and demands of a performance-based education system.